2018
DOI: 10.1186/s12914-018-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

Realization of the right to adequate food and the nutritional status of land evictees: a case for mothers/caregivers and their children in rural Central Uganda

Abstract: BackgroundIn developing countries like Uganda, the human right to adequate food (RtAF) is inextricably linked to access to land for households to feed themselves directly through production or means for its procurement. Whether RtAF is enjoyed among Ugandan land evictees, is unknown. We therefore explored this among land evictees (rights-holders) in Wakiso and Mpigi districts in rural Central Uganda. We assessed food accessibility and related coping strategies, diet quality and nutritional status of children 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
12
0
5
Order By: Relevance
“…Our qualitative study findings can be used to inform the development of tools to measure the impacts of forced eviction and indicate the need to further investigate associations between forced evictions and child health outcomes. The study findings are relevant for a range of similar humanitarian settings where IDPs suffer from forced eviction [ 3 , 15 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our qualitative study findings can be used to inform the development of tools to measure the impacts of forced eviction and indicate the need to further investigate associations between forced evictions and child health outcomes. The study findings are relevant for a range of similar humanitarian settings where IDPs suffer from forced eviction [ 3 , 15 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in low-income countries has shown that women’s health is particularly affected by forced eviction as they may experience psychosocial distress, miscarriages, gender-based violence, undernutrition, overweight, physical injuries or death [ 12–15 ]. Eviction can also contribute to malnutrition and infections such as diarrhoea, respiratory infections, and skin infections in children [ 3 , 15 ]. Qualitative studies suggest that eviction is often experienced by individuals as a personal failure and carries stigma.…”
Section: Introductionmentioning
confidence: 99%
“…After a major landslide disaster in 2010 in the Bududa district of Eastern Uganda, some affected households resettled in the Kiryandongo district in Western Uganda. Food security was not uniform, and those with access to land were most able to access food and income (Nahalomo et al, 2018). Another study demonstrates that factors such as HIV/AIDS status may be a determinant of marginality, aggravating not only the capacity to work and receive income, but also the ability to participate in solidarity networks, enhancing the negative outcomes of marginality for people's food security (Kalofonos, 2010).…”
Section: Advancing the Rights And Capabilities Of Marginalized Groups To Produce And Access Food (D)mentioning
confidence: 99%
“…Protecting the Right to Access Land, Water, and Genetic Resources for Food and Agriculture, or Redistributing These Rights (E) Most studies in this action type (n = 5) involved cases where reduced rights to the means to grow, raise and harvest food negatively impacted FSN. In central Uganda, rampant land evictions due to increased land sales between 2006 and 2014 resulted in widespread insufficient access to food (Nahalomo et al, 2018). In Cameroon, increasingly resource-constrained populations had less access to wild foods that had formerly been important components of their diets; instead, they were increasingly resorting to cheaper (more refined, less nutritious) imported food, or to eating less frequently (Sneyd, 2013).…”
Section: Advancing the Rights And Capabilities Of Marginalized Groups To Produce And Access Food (D)mentioning
confidence: 99%
“…These evictions are justified in the name of promoting area development. 40 A good example is the relocation of the Batwa from Bwindi forests and yet the survival of these people is in the forests. The obligation to protect requires the State to protect individuals" enjoyment of the right to food against violations by third parties.…”
Section: State Obligations Regarding the Right To Foodmentioning
confidence: 99%